Effect of Initial Chemical and Physiological Properties of Fruits of Some Peach Cultivars at Harvest on Fruit Rot development - Alawami, A. M. Y. (Al-Mukhtar Journal of Sciences, 2008)
This research was conducted to study the effect of chemical and physiological properties of fruits of several peach cultivars at harvest (Florda prince, Desert Red, T. snow, T. Sweet, Swilling and Meit Ghamr), on fruit rot development, which caused by Botrytis cinerea, Penicillium expansum and Rhizopus stolonifer, during storage period at room temperature (24-27 C). The result indicated that there were clearing differences between the initial fruit properties of cultivars at harvest time. This may be related to the response of these cultivars to disease development. However, the disease was develop slowly on Miet Ghamr cultivar compared with the other ones, but the disease severity was highly on all cultivars at the end of storage period. Generally, infection with R. stolonifer only started to appear one day after inoculation on all cultivars as compared with the other fungi. In addition, this fungus showed quick progress in lesion diameters and the rot was covered fruit surface after 4 days from inoculation.